MeBib Suppressed Methamphetamine Self-Administration Response via Inhibition of BDNF/ERK/CREB Signal Pathway in the Hippocampus - Kim, Buyun (Biomol Ther (Seoul), 2020)
Methamphetamine (MA) is one of the most commonly abused drugs in the world by illegal drug users. Addiction to MA is a serious public health problem and effective therapies do not exist to date. It has also been reported that behavior induced by psychostimulants such as MA is related to histone deacetylase (HDAC). MeBib is an HDAC6 inhibitor derived from a benzimidazole scaffold. Many benzimidazole-containing compounds exhibit a wide range of pharmacological activity. In this study, we investigated whether HDAC6 inhibitor MeBib modulates the behavioral response in MA self-administered rats. Our results demonstrated that the number of active lever presses in MA self-administered rats was reduced by pretreatment with MeBib. In the hippocampus of rats, we also found MA administration promotes GluN2B, an NMDA receptor subunit, expression, which results in sequential activation of ERK/CREB/BDNF pathway, however, MeBib abrogated it. Collectively, we suggest that MeBib prevents the MA seeking response induced by MA administration and therefore, represents a potent candidate as an MA addiction inhibitor.